2020
DOI: 10.5829/ije.2020.33.07a.15
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Method for Sequential Images–based Process Monitoring

Abstract: Today, with the growth of technology, monitoring processes by the use of video and satellite sensors have been more expanded, due to their rich and valuable information. Recently, some researchers have used sequential images for defect detection because a single image is not sufficient for process monitoring. In this paper, by adding the time dimension to the image-based process monitoring problem, we detect process changes (such as the changes in the size, location, speed, color, etc.). The temporal correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Post conversion, the YCbCr image is processed through mean and median filtering. The processes of mean and median filtering are performed to obtain a more solid image and reduce the noise that may be induced during image segmentation [23].…”
Section: Methodsmentioning
confidence: 99%
“…Post conversion, the YCbCr image is processed through mean and median filtering. The processes of mean and median filtering are performed to obtain a more solid image and reduce the noise that may be induced during image segmentation [23].…”
Section: Methodsmentioning
confidence: 99%
“…Kabiri and Bayati [6] used control charts as important tools of statistical process control in combination with modern tools such as artificial neural networks. Fattahzadeh and Saghaei [7] monitored their processes using image sensors and control charts. Rasay et al [8] showed the application of multivariate control charts in condition-based maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…He also used ANOVA technique for correlation measurment purposes. Fattahzade et al [17] presented the new approach of monitoring using sequential images. They used statistical methods and measured correlation between images for defect detection process.…”
Section: Introductionmentioning
confidence: 99%